2005
DOI: 10.1081/css-200043139
|View full text |Cite
|
Sign up to set email alerts
|

How to Prepare a Good Plant Sample for Internal Reference Material

Abstract: To evaluate their daily work in analytical measurements, all soil analysis laboratories must have their own low-cost reference material to substitute high-cost certified reference materials. This standard can be used to substitute routine use of high-cost certified reference material (CRM). This standard can be used to substitute routine use of CRM or conventionalized reference materials in case the former are not available. This article presents a simple procedure for preparing a standard for plant material t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Nyiredy (3) discussed the necessity of extraction methods to characterize both the volatile and nonvolatile components of these natural products. Similarly, the preparation of internal reference standards of soil and plant samples was proposed (4). Statistical methods to ensure sample homogeneity were investigated, and an interlaboratory validation was performed.…”
Section: General Sample Preparation Considerationsmentioning
confidence: 99%
“…Nyiredy (3) discussed the necessity of extraction methods to characterize both the volatile and nonvolatile components of these natural products. Similarly, the preparation of internal reference standards of soil and plant samples was proposed (4). Statistical methods to ensure sample homogeneity were investigated, and an interlaboratory validation was performed.…”
Section: General Sample Preparation Considerationsmentioning
confidence: 99%
“…Nitrogen was selected as the primary indicator of homogeneity because of its relative ease of determination by the Kjeldahl method. To determine the degree of homogeneity, the mean variance of the nitrogen analysis was calculated and a matrix of coefficients was set-up (Lo'pez-Romero et al, 2005) and the results are shown in Table 1.…”
Section: Homogeneity Testmentioning
confidence: 99%
“…The residue was discarded. Homogenization of the material was carried out by mixing the entire quantity of powder having particle size smaller than 250 µm in a plastic container for 60 h. Sub-samples, N1 to N10 were selected from the bulky sample by random sampling (Lo'pez-Romero et al, 2005). To test sample homogeneity with respect to nitrogen, a mass of 0.5 g of powdered leaves was randomly selected from each sub-sample into a digestion flask followed by determination of total nitrogen by the the Kjeldahl method which was adopted (Willis et al, 1996).…”
Section: Homogenization and Testing Of The Materialsmentioning
confidence: 99%
See 1 more Smart Citation